GRATITUDE INTERVENTION ENHANCES SUBJECTIVE WELL-BEING IN CHINESE SINGLE EMERGING ADULTS: A MIXED STUDY - Yuanhu Ding; Rajitha Menon Arikkatt; Zura R Daoud (The Indonesian Journal of Public Health, 2026)
Introduction: Singlehood is on the rise, According to China's Ministry of Civil Affairs, the number of single adults is projected to exceed 300 million in 2025, accounting for approximately 21.25% of the total population. few studies have investigated how well gratitude intervention training (GIT) can improve single emerging adults' subjective well-being (SWB). Aims: The 6-week GIT intended to improve SWB in Chinese single emerging adults is being empirically evaluated. Methods: A quasi-experimental design was used in this mixed-method study to investigate the acceptability and effectiveness of the 6-week GIT in Chinese single emerging adults (N = 52). A two-group (experimental group and waitlist control group) pretest and posttest methodology was used to develop the quantitative strand. Data analysis was performed via univariate ANCOVA. 12 of the participants in the experimental group were invited to join semi-structured interviews after completion of six sessions. Qualitative data were analyzed via reflexive thematic analysis. Results: After six weeks in the GIT, Chinese single emerging adults' SWB scores significantly increased (F(1,49) = 28.031, p < 0.001, η² = 0.364), and pairwise comparisons via Bonferroni adjustment confirmed a significant difference between the two groups (p < 0.001, 95% CI [0.628, 1.396]). The participants' positive experiences, which demonstrated the acceptability and effectiveness of the GIT, supported the results. Conclusion: This study positively validated the effect of a 6-week GIT on SWB in Chinese single emerging adults.